Comparison of flow structures in the wake region of two similar normal flat plates in tandem and a square cylinder - Hacisevki, H.; Teimourian, A. (Elsevier Science Inc, 2015)
Flow structures and downstream wake behind two identical tandem flat plates and a square cylinder has been studied at high Reynolds number and similarities and dissimilarities in coherent and incoherent structures have been identified. It was found that the square cylinder produces higher coherent turbulence kinetic energy (TKE) with peaks up to seven times higher than the flat plates in tandem. Also, turbulence kinetic energy production contours revealed that while the turbulent peak occurs mainly at the edges of the normal flat plates in tandem, it develops at centreline in the wake of the square cylinder. Interestingly, it was observed that the square cylinder exhibits two alternative shedding frequencies along centreline in the wake region. (C) 2015 Elsevier Inc. All rights reserved.
Keywords: Tandem flat plates; Square cylinder; Coherent and Incoherent; Wake